The Viral Network : A Pathography of the H1N1 Influenza Pandemic - MacPhail, Theresa, 1972- (Book collections on Project MUSE., 2014)
"In The Viral Network, Theresa MacPhail examines our collective fascination with and fear of viruses through the lens of the 2009 H1N1 pandemic. In April 2009, a novel strain of H1N1 influenza virus resulting from a combination of bird, swine, and human flu viruses emerged in Veracruz, Mexico. The Director-General of the World Health Organization (WHO) announced an official end to the pandemic in August 2010. Experts agree that the global death toll reached 284,500. The public health response to the pandemic was complicated by the simultaneous economic crisis and by the public scrutiny of official response in an atmosphere of widespread connectivity. MacPhail follows the H1N1 influenza virus's trajectory through time and space in order to construct a three-dimensional picture of what happens when global public health comes down with a case of the flu"--